LGBTQ and religious identity conflict in service settings. Issue 4 (10th July 2017) - Minton, Elizabeth A.; Cabano, Frank; Gardner, Meryl; Mathras, Daniele; Elliot, Esi; Mandel, Naomi
Abstract : Purpose: The USA is witnessing a conflict between LGBTQ (lesbian, gay, bisexual, transgender and queer) consumers/supporters and Christian fundamentalist service providers/opponents regarding whether service can be denied based on religious values. The purpose of this paper is to make a timely investigation into this conflict between marketplace inclusion (for LGBTQ consumers) and freedom of religion (for religious service providers). Design/methodology/approach: The intersection of marketplace inclusion for LGBTQ consumers and religious freedom for service providers is examined by identifying appropriate strategies that address this conflict and reviewing how differing religious perspectives influence perceptions of LGBTQ consumer rights, all building off the social identity threat literature. Findings: LGBTQ and religious identities often conflict to influence consumer behavior and service provider interactions. Such conflict is heightened when there is a lack of substitutes (i.e. only one service provider in an area for a specific service). Common LGBTQ consumer responses include changing service providers, providing justification for the provision of services and pursing legal recourse. Suggested strategies to address this conflict include highlighting common social identities and using two-sided messages for service providers, using in-group interventions for social groups and using government interventions for public policy. Originality/value: Research has yet to examine the conflict between marketplace inclusion and religious freedom, particularly for the inclusion of LGBTQ consumers. Thus, this paper provides a novel conceptual model detailing these relationships to stimulate discussion among consumers, service providers, social groups and public policy in addition to serving as a foundation for future research.